2017
DOI: 10.3389/fpls.2017.01001
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Enhances High-Salinity Stress Tolerance by Detoxifying Reactive Oxygen Species in Arabidopsis thaliana and Rice

Abstract: High-salinity stress considerably affects plant growth and crop yield. Thus, developing techniques to enhance high-salinity stress tolerance in plants is important. In this study, we revealed that ethanol enhances high-salinity stress tolerance in Arabidopsis thaliana and rice. To elucidate the molecular mechanism underlying the ethanol-induced tolerance, we performed microarray analyses using A. thaliana seedlings. Our data indicated that the expression levels of 1,323 and 1,293 genes were upregulated by etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 32 publications
9
62
0
Order By: Relevance
“…Numerous studies have found that implementing exogenous chemicals improves salt stress tolerance in plants [13]; examples of such chemicals are phytohormones such as salicylic acid, sterols, and methyl jasmonate [2,14]. Other chemicals such as polyamines, melatonin, and sodium nitroprusside have also been used to enhance the tolerance of various crop plants to saline conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that implementing exogenous chemicals improves salt stress tolerance in plants [13]; examples of such chemicals are phytohormones such as salicylic acid, sterols, and methyl jasmonate [2,14]. Other chemicals such as polyamines, melatonin, and sodium nitroprusside have also been used to enhance the tolerance of various crop plants to saline conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa) is one of the most important food crops for humans, and different abiotic stresses can affect plant growth and crop performance [1,2]. Salinity stress has a strong negative influence on plant growth [3,4]. Drought represents an extreme environment, and causes irreversible damage to rice growth and lowers crop yield and quality [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, ADH1 activity could be coordinated with CSD1 activity to modulate the levels of NAD + and other redox molecules involved in maintaining an appropriate balance under stress conditions. Additionally, ethanol produced by ADH1 activity could serve as a signal to bolster plant responses to water deficit, as it has recently been suggested for Arabidopsis, where addition of external ethanol helped plants to better cope with saline stress conditions, by enhancing gene regulation responses and ROS scavenging activities (Nguyen et al, ).…”
Section: Discussionmentioning
confidence: 99%